First observation of PeV-energy neutrinos with IceCube. - Aartsen, MG; Abbasi, R; Abdou, Y; Ackermann, M; Adams, J; Aguilar, J; Ahlers, M; Altmann, D; Auffenberg, J; Bai, X; Baker, M; Barwick, S; et al. (2013)
We report on the observation of two neutrino-induced events which have an estimated deposited energy in the IceCube detector of 1.04±0.16 and 1.14±0.17 PeV, respectively, the highest neutrino energies observed so far. These events are consistent with fully contained particle showers induced by neutral-current ν(e,μ,τ) (ν(e,μ,τ)) or charged-current ν(e) (ν(e)) interactions within the IceCube detector. The events were discovered in a search for ultrahigh energy neutrinos using data corresponding to 615.9 days effective live time. The expected number of atmospheric background is 0.082±0.004(stat)(-0.057)(+0.041)(syst). The probability of observing two or more candidate events under the atmospheric background-only hypothesis is 2.9×10(-3) (2.8σ) taking into account the uncertainty on the expected number of background events. These two events could be a first indication of an astrophysical neutrino flux; the moderate significance, however, does not permit a definitive conclusion at this time.